Inhibitory effects of saffron compounds on multiple sclerosis: Molecular docking and dynamic, enhancing properties with gold nanoparticles and evaluating antioxidant, antibacterial, cytotoxicity - Shaghayegh Mohammadi; Hamed Farjam; Sharieh Hosseini; Kambiz Larijani (Heliyon)
The unique properties of nanoparticles, such as their small size and the ability to cross the blood-brain barrier, make them well-suited for targeted drug delivery to the central nervous system. Ongoing research is dedicated to developing innovative nanoparticle-based therapies for a neurological disorder; multiple sclerosis (MS). The study confirmed green synthesis as the optimal method for producing environmentally friendly compounds. The nanoparticles were characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray powder diffraction (XRD), and transmission electron microscopy (TEM). To evaluate the antioxidant properties, we employed the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, while conducting a comprehensive examination of antibacterial activity against both Gram-negative (E. coli) and Gram-positive bacteria (S. aureus). Moreover, we performed a thorough assessment of cellular toxicity using saffron extracts and nanoparticles on C6 and SH-SY5Y cells. We employed molecular docking computational methods to investigate the potential inhibitory effects of natural compounds derived from saffron on Multiple Sclerosis. The results of biological activities and computational modeling show that gold nanoparticles improve the performance of plant compounds and also these compounds can be involved in inhibiting proteins responsible for multiple sclerosis.